Cardiac impairment in Long Covid 1-year post SARS-CoV-2 infection. (3rd October 2022) - Roca-Fernandez, A; Wamil, M; Telford, A; Carapella, V; Borlotti, A; Monteiro, D; Thomaides-Brears, H; Dennis, A; Banerjee, R; Robson, M D; Lip, G Y H; Bull, S; et al.
Abstract: Background: Long Covid is associated with multiple symptoms and impairment in multiple organs [1]. Cardiac impairment has been reported to varying degrees by varying methodologies in cross-sectional studies. Using cardiovascular magnetic resonance (CMR), we investigated the 12-month trajectory of cardiac impairment in individuals with Long Covid. Purpose: We conducted a prospective, longitudinal, 1-year study in individuals with Long Covid to investigate 1) the characteristics and trajectory of cardiac impairment; 2) the impact of acute hospitalisation for COVID-19 on cardiac impairment; and 3) pathways for designing and improving clinical management for individuals at risk of cardiac impairment. Methods: 534 individuals with Long Covid underwent baseline CMR (quantitative T1 and T2 mapping, cardiac mass, volumes, function, and strain) and multi-organ MRI at 6 months (IQR 4.3, 7.3) since first post-COVID-19 symptoms. If abnormal findings were reported at baseline, individuals were rescanned at 12.6 months (IQR 11.4, 14.2) (n=330). Symptoms, standardised questionnaires, and blood samples were collected at both timepoints (Figure 1). Cardiac impairment was defined as one or more of: low left or right ventricular ejection fraction (LVEF and RVEF), high left or right ventricular end diastolic volume (LVEDV and RVEDV), impaired left ventricular global longitudinal strain (GLS), or elevated native T1 in ≥3 cardiac independent AHA segments. A significant change over time was reported by comparison with 92 healthy controls. Results: The technical success of this multiorgan assessment in a non-acute setting was 99.1% at baseline, and 98.3% at follow-up, with 99.6% and 98.8% for CMR, respectively. Of individuals with Long Covid, 19% had cardiac impairment at baseline; 70% had complete paired data at 12 months. Of those with paired data, 58% presented with ongoing cardiac impairment at 12 months. High sensitivity cardiac troponin I and B-type natriuretic peptide were not predictive of CMR findings, symptoms, or clinical outcomes. At baseline, low LVEF, high RVEDV and reduced GLS were associated with cardiac impairment; however, while elevated T1 was associated with less symptom severity at 12 months, individuals with low LVEF at baseline were associated with ongoing cardiac impairment 1 year post-infection (Figure 2). Conclusion: Cardiac impairment, other than myocarditis, is present in 1 in 5 individuals with Long Covid at 6 months, persisting in over half of those at 12 months. Cardiac-related blood biomarkers are unable to identify cardiac impairment in Long COVID. Subtypes of disease (based on symptoms, examination, and investigations) and predictive biomarkers are yet to be established. Interventional trials with pre-specified subgroup analyses are required to inform therapeutic options. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): Radical (EU) and Innovative UK (UK national) (and others)